How to address data privacy concerns when using social media data in conservation science - Di Minin, Enrico; Fink, Christoph; Hausmann, Anna; Kremer, Jens; Kulkarni, Ritwik (Conservation biology, 2021)
Social media data are being increasingly used in conservation science to study human–nature interactions. User‐generated content, such as images, video, text, and audio, and the associated metadata can be used to assess such interactions. A number of social media platforms provide free access to user‐generated social media content. However, similar to any research involving people, scientific investigations based on social media data require compliance with highest standards of data privacy and data protection, even when data are publicly available. Should social media data be misused, the risks to individual users' privacy and well‐being can be substantial. We investigated the legal basis for using social media data while ensuring data subjects’ rights through a case study based on the European Union's General Data Protection Regulation. The risks associated with using social media data in research include accidental and purposeful misidentification that has the potential to cause psychological or physical harm to an identified person. To collect, store, protect, share, and manage social media data in a way that prevents potential risks to users involved, one should minimize data, anonymize data, and follow strict data management procedure. Risk‐based approaches, such as a data privacy impact assessment, can be used to identify and minimize privacy risks to social media users, to demonstrate accountability and to comply with data protection legislation. We recommend that conservation scientists carefully consider our recommendations in devising their research objectives so as to facilitate responsible use of social media data in conservation science research, for example, in conservation culturomics and investigations of illegal wildlife trade online. Cómo Abordar las Preocupaciones por Privacidad al Usar las Redes Sociales en las Ciencias de las Conservación Resumen Cada vez se usan más los datos de las redes sociales en las ciencias de la conservación para estudiar las interacciones humano‐naturaleza. El contenido generado por usuarios (imágenes, videos, textos y audios) y los metadatos asociados a estos pueden usarse para evaluar dichas interacciones. Un gran número de redes sociales proporcionan acceso gratuito al contenido generado por usuarios en las redes sociales. Sin embargo, como con cualquier investigación que involucre personas, las investigaciones basadas en los datos obtenidos de la redes sociales requieren cumplir con los estándares más altos de privacidad de datos y protección de la información, incluso cuando éstos están disponibles públicamente. En caso de que se le dé un uso inapropiado a la información obtenida de las redes sociales, los riesgos para la privacidad del usuario y para su bienestar pueden ser sustanciales. Investigamos las bases legales para el uso de la información de redes sociales en conjunto con la garantía de derechos para los sujetos de la información por medio de un estudio de caso basado en la Regulación de la Protección de Datos Generales (GDPR) de la Unión Europea (EU). Los riesgos asociados con el uso de información de las redes sociales en la investigación incluyen la identificación errónea accidental o intencional, la cual tiene el potencial de ocasionar daño psicológico o físico a la persona identificada. Para recolectar, almacenar, proteger, compartir y administrar la información de las redes sociales de manera que se prevengan los riesgos potenciales para los usuarios involucrados, se deben minimizar los datos, volverlos anónimos y seguir un procedimiento estricto de manejo de datos. Las estrategias basadas en riesgos, como la evaluación del impacto de la privacidad de datos, pueden usarse para identificar y minimizar los riesgos de privacidad presentes para los usuarios de las redes, para demostrar responsabilidades y para cumplir con la legislación de protección de datos. Recomendamos a los científicos de la conservación que consideren con cuidado nuestras recomendaciones para el diseño de sus objetivos de investigación para así facilitar el uso responsable de la información de redes sociales en la investigación de las ciencias de la conservación, por ejemplo para las investigaciones sobre el mercado ilegal de fauna en línea y para la culturomia de la conservación. 摘要 社交媒体数据正越来越多地用于保护科学, 以研究人类与自然的互动。用户发布的内容如图像、视频、文本、音频以及相关的元数据可用于评估此类互动。许多社交媒体平台都可以自由访问用户发布的社交媒体内容。然而, 与其它涉及人类的研究一样, 基于社交媒体数据的科学研究需要遵守数据隐私和数据保护的最高标准, 即使使用的是公开数据。如果社交媒体数据被滥用, 个人用户的隐私和福祉将面临巨大风险。我们通过基于欧盟《通用数据保护条例》的案例研究, 研究了在确保数据主体权利的同时使用社交媒体数据的法律依据。在研究中使用社交媒体数据的风险包括有意和无意的错误识别, 这有可能对被识别个体造成心理或身体上的伤害。在收集、存储、保护、共享和管理社交媒体数据时, 为了避免对用户的潜在风险, 应做到数据最小化、数据匿名化并遵守严格的数据管理流程。基于风险的方法, 如数据隐私影响评估, 也可用于识别和减少社交媒体用户的隐私风险、说明责任归属和遵从数据保护法规。我们建议从事保护的科学家在制定研究目标时仔细考虑我们的建议, 以便在保护科学研究中以负责任的方式使用社交媒体数据, 例如在保护文化组学和在线调查非法野生动物贸易等方面。【翻译 :胡怡思 ;审校 :聂永刚】 Article impact statement: Collecting, storing, protecting, sharing, and managing social media data should be done in a manner that prevents potential risks to users.